The assessment of biodiversity changes and sustainable agricultural development in the Beijing-Tianjin-Hebei Region of China - Liao, Meizhe; Zhang, Zongwen; Yan, Ruirui; Bai, Keyu (MDPI, 2024)
In the face of a series of challenges, such as climate change, population growth, and agricultural intensification, as well as the issue of how to promote sustainable development and guarantee food security, biodiversity, with its unique genetic, ecological, and traditional socio-cultural values, has become an important way to solve this dilemma. Urban biodiversity has continued to decline in recent decades due to rapid urbanization. The agroecosystem health of the Beijing-Tianjin-Hebei region, a typical urban agglomeration economic area, is facing a critical situation. Therefore, assessing the potential of ecosystem diversity in the Beijing-Tianjin-Hebei region and exploring the assessment mechanisms and methods of ecosystem health can provide theoretical support for biodiversity conservation and utilization. In this thesis, the overall ecosystem health of the Beijing-Tianjin-Hebei region was assessed based on the land cover data from 1992 to 2022 and the projected land cover data up to 2032, as well as using the habitat quality indicated by the Fragstats and InVEST models and the landscape pattern index, habitat quality, and mean species abundance (MSA) indicators of the GLOBIO module. The main results are as follows: Habitat quality and mean species abundance (MSA) in the Beijing-Tianjin-Hebei region were observed to show a continuous downward trend over 40 years from a landscape level perspective, and landscape fragmentation due to urbanization was the main reason. Habitat loss and habitat degradation caused by landscape fragmentation led to a decline in biodiversity. The spatial distribution of habitat quality in the Beijing-Tianjin-Hebei region is closely correlated with topography and landscape, being higher in the northwest and lower in the southeast, forming a clear spatial pattern that declined from 0.599 to 0.564 between 1992 and 2032. The mean species richness (MSA) value of the Beijing-Tianjin-Hebei region is significantly affected by infrastructure, especially road construction. With the continuous expansion of the road network, the MSA values in the region generally show a decreasing trend from 0.270 to 0.183 between 1992 and 2032. Based on the above results, it is recommended to carry out several aspects of agrobiodiversity conservation and ecosystem restoration.